High efficacy of Sofosbuvir plus Simeprevir in a large cohort of Spanish cirrhotic patients infected with genotypes 1 and 4. (5th June 2017) - Mariño, Zoe; Pascasio‐Acevedo, Juan M.; Gallego, Adolfo; Diago, Moisés; Baliellas, Carme; Morillas, Rosa; Prieto, Martín; Moreno, José M.; Sánchez‐Antolín, Gloria; Vergara, Mercedes; Forné, Montserrat; Fernández, Inmaculada; et al.
Abstract: Background and Aims: Hepatitis C (HCV) therapy with Sofosbuvir (SOF)/Simeprevir (SMV) in clinical trials and real‐world clinical practice, showed high rates of sustained virological response (SVR) in non‐cirrhotic genotype (GT)‐1 and GT‐4 patients. These results were slightly lower in cirrhotic patients. We investigated real‐life effectiveness and safety of SOF/SMV with or without ribavirin (RBV) in a large cohort of cirrhotic patients. Methods: This collaborative multicentre study included data from 968 patients with cirrhosis infected with HCV‐GT1 or 4, treated with SOF/SMV±RBV in 30 centres across Spain between January‐2014 and December‐2015. Demographic, clinical, virological and safety data were analysed. Results: Overall SVR was 92.3%; the majority of patients were treated with RBV (62%) for 12 weeks (92.4%). No significant differences in SVR were observed between genotypes (GT1a:94.3%; GT1b:91.7%; GT4:91.1%). Those patients with more advanced liver disease (Child B/C, MELD≥10) or portal hypertension (platelet count≤100×10 9 /L, transient elastography≥21 Kpa) showed significantly lower SVR rates (84.4%‐91.9%) than patients with less advanced liver disease (93.8%‐95.9%, P <.01 in all cases). In the multivariate analysis, the use of RBV, female gender, baseline albumin≥35 g/L, MELD<10 and lack of exposure to a triple therapy regimen were independent predictors of SVR ( P <.05). Serious adverse events (SAEs) and SAE‐associated discontinuation events occurred in 5.9% and 2.6%. Conclusions: In this large cohort of cirrhotic patients managed in the real‐world setting in Spain, SOF/SMV±RBV yielded to excellent SVR rates, especially in patients with compensated liver cirrhosis. In addition, this combination showed to be safe, with low rates of SAEs and early discontinuations.